Current Chemical, Biological, and Physiological Views in the Development of Successful Brain-Targeted Pharmaceutics - Markowicz-Piasecka, Magdalena; Markiewicz, Agata; Darłak, Patrycja; Sikora, Joanna; Adla, Santosh Kumar; Bagina, Sreelatha; Huttunen, Kristiina M (Neurotherapeutics, 2022)
One of the greatest challenges with successful pharmaceutical treatments of central nervous system (CNS) diseases is the delivery of drugs into their target sites with appropriate concentrations. For example, the physically tight blood-brain barrier (BBB) effectively blocks compounds from penetrating into the brain, also by the action of metabolizing enzymes and efflux transport mechanisms. However, many endogenous compounds, including both smaller compounds and macromolecules, like amino acids, sugars, vitamins, nucleosides, hormones, steroids, and electrolytes, have their peculiar internalization routes across the BBB. These delivery mechanisms, namely carrier-mediated transport and receptor-mediated transcytosis have been utilized to some extent in brain-targeted drug development. The incomplete knowledge of the BBB and the smaller than a desirable number of chemical tools have hindered the development of successful brain-targeted pharmaceutics. This review discusses the recent advancements achieved in the field from the point of medicinal chemistry view and discusses how brain drug delivery can be improved in the future.
Keywords: biologický transport; Brain-blood barrier; Central Nervous System Diseases; biofarmacie; Prodrug approach; lidé; Blood-Brain Barrier; mozek; Carrier-mediated transport; hematoencefalická bariéra; Drug delivery; Biological Transport; Receptor-mediated transport; Brain; nemoci centrálního nervového systému; Drug Delivery Systems; Biopharmaceutics; lékové transportní systémy; Humans